Towards Computational Screening for New Energetic Molecules: Calculation of Heat of Formation and Determination of Bond Strengths by Local Mode Analysis - Christopher, Imogen L.; Michalchuk, Adam A. L.; Pulham, Colin R.; Morrison, Carole A. (Frontiers in Chemistry, 2021)
The reliable determination of gas-phase and solid-state heats of formation are important considerations in energetic materials research. Herein, the ability of PM7 to calculate the gas-phase heats of formation for CNHO-only and inorganic compounds has been critically evaluated, and for the former, comparisons drawn with isodesmic equations and atom equivalence methods. Routes to obtain solid-state heats of formation for a range of single-component molecular solids, salts, and co-crystals were also evaluated. Finally, local vibrational mode analysis has been used to calculate bond length/force constant curves for seven different chemical bonds occurring in CHNO-containing molecules, which allow for rapid identification of the weakest bond, opening up great potential to rationalise decomposition pathways. Both metrics are important tools in rationalising the design of new energetic materials through computational screening processes.